Cover Picture: Iridium(III)‐Doped Core‐Shell Silica Nanoparticles: Near‐IR Electrogenerated Chemiluminescence in Water (ChemElectroChem 7/2017). Issue 7 (21st June 2017) - Kesarkar, Sagar; Rampazzo, Enrico; Valenti, Giovanni; Marcaccio, Massimo; Bossi, Alberto; Prodi, Luca; Paolucci, Francesco
Abstract : The Front Cover picture exemplifies nanoparticles with a silica core and PEG shell (Plus NPs) encapsulating transition‐metal complexes (dyes), generating emission in aqueous medium in the presence of a co‐reactant on a platinum electrode surface. More information can be found in the Article by F. Paolucci and co‐workers onpage 1690 in Issue 7, 2017 (DOI:10.1002/celc.201700071 ).